From Integration of Islam-State to Integration of Ummah-State: The Biography of Buya Hamka - Fata, Ahmad Khoirul; Fauzan, Pepen Irpan; Izzuddin , Izzuddin (Journal of Al-Tamaddun, 2024)
This article discusses Haji Abdul Malik Karim Amrullah (HAMKA) as a political figure. The discussion is centered on his political role during the Parliamentarian Democracy, Guided Democracy, and the New Order eras. Historical-biography approach is employed in this study as there were very few of literature on Hamka as an activist of political movement. Current studies on Hamka is heavily focused on his figure as an Ulama and a litterateur. Hamka’s role as a political activist, either in political practices or in the process of influencing public policy are often neglected. This study concluded that in general, Hamka’s political actions are aimed to make Islam and Islamic ummah as an important factor for Indonesia as a state. Hamka interpreted this objective into various actions based on the challenge of the era. During the parliamentarian era, Hamka’s political movement was aimed at integrating Islam into Indonesian Constitution. Whereas during the Guided-Democracy era, his political actions were intended to protect the ummah from anti-religious ideology (communism) that strongly dominated the state power at that time. Finally, in the New Order era, Hamka’s political movement were intended to integrate Islamic ummah into the process of the state life.